Supporting adolescent well-being at school: Integrating transformative social and emotional learning and trauma-informed education - Jacqueline E. Maloney; Jenna Whitehead; David Long; Julia Kaufmann; Eva Oberle; Kimberly A. Schonert-Reichl; Michelle Cianfrone; Alexander Gist; Hasina Samji (Social and Emotional Learning: Research, Practice, and Policy)
There is an urgent need to support the social and emotional well-being of adolescents with experiences of adversity and trauma. Adolescence is a critical period of development for promoting social and emotional competencies, which can prevent poor mental health and problematic substance use and promote thriving during challenging teenage years and beyond. Both transformative social and emotional learning (TSEL) and trauma-informed programs for schools (TIPS) have been identified as promising practices for supporting social and emotional well-being among young people with experiences of adversity. We propose a pragmatic theory of action for schools for implementing and evaluating initiatives that integrate TSEL and TIPS made up of three iterative components: awareness, assessment, and action. The TSEL + TIPS Theory of Action is illustrated by a case study of a cross-sectoral collaboration of government, schools, researchers, healthcare, and adolescents to implement TSEL and TIPS initiatives in British Columbia, Canada. The case study provides evidence for the feasibility of TSEL + TIPS Theory of Action and may serve as an example for other regions as experiences of adversity and poor mental health continue to rise among adolescents globally.